Human-climate interactions shape fire regimes in the Cerrado of São Paulo state, Brazil - Conciani, Dhemerson E. [UNESP]; Santos, Lucas Pereira dos; Silva, Thiago Sanna Freire; Durigan, Giselda; Alvarado, Swanni T. (Elsevier, 2021)
The Cerrado is the most diverse tropical savanna in the world. As a fire-prone ecosystem, natural fire in the Cerrado shapes plant communities and drives evolutionary processes. Human activities and landscape management can alter natural fire regimes and reshape Cerrado dynamics, making biodiversity conservation a challenge, particularly in densely populated areas. We reconstructed the historical fire regime of three protected areas (PA) and their buffer zones in São Paulo state to understand how current fire exclusion policies are affecting fire regimes and to measure how human-climate-fire relationships can change in areas under different land management. We used Landsat satellite imagery, from 1984 to 2017, with 30 m of spatial resolution and 16 days of temporal resolution. In total, we mapped 49,471 ha of burned area, and we detected variations in fire frequency and fire size among sites. PA dominated by open savanna in Itirapina concentrated 93 % of all observed fires, while PA dominated by forest-like formations in Assis represented only 2% of the fires. Annual rainfall showed a very weak relationship (R2 = 0.04) with annual total burned area, while the rainfall split between dry and wet seasons showed a tendency to have a fuel moisture effect which determined the vegetation available to burn in the dry season (R² = 0.09). Fire regimes in PA were similar to those observed in buffer zones suggesting that fire-exclusion policies do not effectively prevent fires in PA that are surrounded by an anthropic matrix where fire is often used. When we included human factors in addition to rainfall, our models explained 44 % of variation of burned areas. We conclude that fire regimes in São Paulo Cerrado have been modified by humans and that fire exclusion is not a suitable policy for protected areas in this fire-prone ecosystem.
Keywords: Anthropic landscapes; Fire management; Forestry; Landsat; Protected areas; Savannas